2022
DOI: 10.1371/journal.pone.0263451
|View full text |Cite
|
Sign up to set email alerts
|

Congenital malaria: Frequency and epidemiology in Colombia, 2009-2020

Abstract: Congenital Malaria (CM) is an underestimated and under-researched problem in Colombia, despite its severe clinical, epidemiological, economic, and public health consequences. The objective was to determine the general frequency of CM, the specific frequency of CM by diagnostic test and plasmodial species, and identify its associated factors. A retrospective study was carried out using the records of 567 newborns. qPCR and Thick Blood Smear (TBS) were performed. The frequency of infection was determined with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
1
5
0
2
Order By: Relevance
“…In a recent study, done in Colombia, all CM cases were found to be submicroscopic with a frequency of 12.2% infections. [ 32 ] Here, submicroscopic refers to negative with Thick Blood Smear and positive with PCR. The same study showed better yield with umbilical cord blood as compared to peripheral blood (16.2% vs 2.2%.…”
Section: Diagnosismentioning
confidence: 99%
“…In a recent study, done in Colombia, all CM cases were found to be submicroscopic with a frequency of 12.2% infections. [ 32 ] Here, submicroscopic refers to negative with Thick Blood Smear and positive with PCR. The same study showed better yield with umbilical cord blood as compared to peripheral blood (16.2% vs 2.2%.…”
Section: Diagnosismentioning
confidence: 99%
“…24 Manajemen malaria pada wanita hamil signifikan dapat mengurangi risiko maternal anemia diantaranya dengan melakukan pemeriksaan ANC secara rutin untuk memantau kondisi ibu dan janin, penggunaan kelambu berinsektisida untuk mencegah gigitan nyamuk, 27 pemeriksaan Hb secara rutin sebulan sekali dan pemberian tablet zat besi selama kehamilan, 28 asam folat, pemberian chloroquine pada kunjungan pertama ANC sampai dengan masa nifas, efektivitas pemberian tiga dosis sulfadoxine pyrimethamine yang direkomendasikan WHO terbukti efektif untuk mencegah malaria selama kehamilan. 29,30,31…”
Section: A Maternal Anemiaunclassified
“…7 Parasit malaria yang ditemukan dalam darah pada tali pusat signifikan lebih tinggi dibandingkan darah tepi bayi baru lahir. 31 Terdeteksinya malaria dalam plasenta dan infeksi malaria dalam setahun terakhir menunjukkan hubungan yang signifikan dengan malaria kongenital. Insiden kongenital malaria yang dilaporkan sangat bervariasi antara 7% sampai dengan 33% pada daerah endemis malaria.…”
Section: B Malaria Kongenitalunclassified
“…In Colombia, there are few clinical studies on PAM. Some epidemiological antecedents reported a high frequency of GM (35.8%), PM (27.7%), and CM (12.2%), associated with a higher risk of maternal anemia and lower birth weight [ 8 , 9 , 10 ]. In clinical practice guidelines for malaria, the clinical aspects of PAM are cited from WHO and CDC reports [ 11 ].…”
Section: Introductionmentioning
confidence: 99%